Analisis penggunaan model CIRC berbantuan wayang animasi pada pembelajaran menulis cerita peserta didik kelas v sd - Inggit Putri Resti Wardani; Siti Istiyati; Septi Yulisetiani (Didaktika Dwija Indria, 2026)
This study aims to describe how the use of the CIRC model assisted by animated wayang in learning to write stories and the writing skills of students in writing stories with the CIRC model assisted by animated wayang. The research approach used in this research is a case study which is included in qualitative research. This research uses data sources namely teachers and students of grade V of SD Negeri Glawan along with the learning process and documents. This research uses a sampling technique, namely purposive sampling. The data collection techniques used in this research are observation, interview, and documentation. The data validity test technique used in this research is triangulation technique and time triangulation. The data analysis technique used Miles and Huberman, namely data collection, data reduction, data presentation, and conclusing drawing/verification. The result of this study is, first that the use of the CIRC (Cooperative Integrated Reading and Composition) model assisted by animated wayang in learning to write stories of fifth grade students of Glawan State Elementary School was carried out in accordance with the CIRC model syntax, and the story writing learning process ran smoothly. Second, the story writing skills of fifth-grade students at Glawan Public Elementary School who used the CIRC model assisted by animated wayang in story writing lessons showed that 72% of students were in the excellent category based on an analysis of their work. It was also found that the results of students' work in writing stories in groups.